Pengaruh Experiential Marketing, Emotional Branding Dan Citra Merek Terhadap Loyalitas Merek (Survei Konsumen Operator Simpati Di Yogyakarta) - Rido, Elen; Wibowo, Sutrisno (Jurnal Manajemen Bisnis, 2016)
This study aimed to determine the empirical evidence about the influence of experiential marketing, emotional branding and brand image on brand loyalty simultaneously. In addition to knowing the influence of experiential marketing to brand loyalty, emotional branding to brand loyalty and brand image on brand loyalty.This study was conducted on people of Yogyakarta are using the provider Simpati. The number of samples in this study 75 respondents. The sampling technique used was purposive sampling where samples were taken based on predetermined criteria. The criteria are the people of Yogyakarta are using the provider Simpati over 3 years. Methods of data collection using questionnaires distributed to the people of Yogyakarta. Simpati Provider related variables experiential marketing, emotional branding, brand image and brand loyalty.Based on the test results t variable experiential marketing and emotional branding does not have a significant effect on brand loyalty, while brand image variables have a significant effect on brand loyalty. Based on F test results indicate that the variable experiential marketing, emotional branding and brand image simultaneous effect on brand loyalty sympathy in Yogyakarta.